2010
DOI: 10.1378/chest.09-3006
|View full text |Cite
|
Sign up to set email alerts
|

Workshop on Idiopathic Pulmonary Fibrosis in Older Adults

Abstract: T he aging lung loses mass and undergoes several functional and structural changes ( Table 1 ). Lung function declines with age, as shown by changes in gas exchange and airfl ow limitation ( Fig 1 ). Older adults, defi ned as those aged Ն 60 years, become more rapidly limited during exercise, and 50% of adults . 70 years of age become exercise-limited by dyspnea, compared with only 20% of younger adults. Abbreviations: EBV 5 Epstein-Barr virus; EMT 5 epithelial-mesenchymal transition; ER 5 endoplasmic reticulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 102 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…A recent study showed that prevalence of IPF increased 50-to 60-fold when comparing adults less than 35 years of age with those over 75 years of age (1,2). However, the pathogenic mechanisms involved in the higher susceptibility of aging individuals to lung fibrosis are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that prevalence of IPF increased 50-to 60-fold when comparing adults less than 35 years of age with those over 75 years of age (1,2). However, the pathogenic mechanisms involved in the higher susceptibility of aging individuals to lung fibrosis are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Its cause is unknown, and there is not a proven effective therapy other than lung transplantation. The prevalence of IPF increases with age, with most patients aged more than 60 years (1,2). IPF remains a progressive, irreversible, and lethal disease with a median survival from 3 to 5 years after the diagnosis.…”
mentioning
confidence: 99%
“…Aging has long been considered a central player in many chronic diseases and recently has been implicated as a major cofactor in the development of IPF (12,69), with evidence suggesting that the aged lung is at greater risk for the development of lung fibrosis following injury (57,69). Interestingly, aging leads to both a decline in protein folding ability in cells and in impaired ability of UPR responses to maintain cellular homeostasis in the setting of ER stress (54,55).…”
Section: Effects Of Aging On Er Stress Responses In the Lungsmentioning
confidence: 99%
“…Age is a significant risk factor for the development of idiopathic pulmonary fibrosis (IPF): people older than 75 years have 50 times higher prevalence than people 35 years old or younger (1)(2)(3). The median age of diagnosis of IPF is approximately 66 years (4,5).…”
Section: Introductionmentioning
confidence: 99%